Konstruksi Bahasa dan Identitas Budaya Jawa dalam Konten Horor Digital: Kajian Representasi Stuart Hall (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
This study examines language and cultural representation to reveal how the Javanese language functions as an identity marker for Javanese people in digital discourse by identifying the representation of Javanese as a mother tongue in digital horror content on the YouTube channel “Jagading Lelembut”, exploring the cultural identity constructed through this representation, and assessing opportunities for the Javanese language’s sustainability. Employing a descriptive-qualitative method and Stuart Hall’s representational approach, this study found three key contexts. In the linguistic context, this content uses specific terms to represent the supernatural world, including alam bokoh, dhemit, and pocongan. It also references Javanese folklore, including wayang characters such as Arjuna, Duryudana, and Banowati. The narrative integrates both ngoko and krama language forms. Ngoko is primarily used to narrate stories for communicative purposes, while krama appears in dialogues to address elders, respected figures, supernatural entities, or during ritual speech. In the context of cultural identity, this content uses specific terms such as lelembut and murca, denoting mystical experiences that are most authentically conveyed through the Javanese language. Meanwhile, wayang, dalang, and jaran kore serve as symbolic manifestations of Javanese cultural representation. This context also encompasses cultural values, as evidenced by narratives that embody spiritual values and respect for inanimate objects, as well as the concept of ‘nrima ing pandum’ that opposes greed. In the context of sustainability in the digital era, this content can potentially broaden the audience for Javanese language and culture, acting as a conduit between contemporary society and Javanese cultural heritage. The findings indicate that the “Jagading Lelembut” channel exemplifies a cultural construction practice that integrates linguistic elements, traditional symbols, and moral values to reinforce Javanese language and its identity in the digital age.